Trends in Personal Income Tax and Employee Social Security Contribution Schedules - Torres, Carolina (OECD Taxation Working Papers, 2012)
Policymakers cannot directly adjust the tax burden of labour income, but they can reform the statutory elements of the tax system, which ultimately determine average and marginal tax rates. To shed light on the determinants of average and marginal personal tax rates, this paper discusses historical and cross-country trends in statutory personal income tax rates, the income thresholds where personal income tax and employee social security contribution rates apply, and other statutory provisions that shape the tax burden on labour income in OECD countries. Trends in the difference between statutory, average and marginal personal income tax rates are also analysed and graphically illustrated. The impact of employee social security contributions on top marginal personal tax rates is also discussed. The most pronounced trend that emerged from 2000 to 2010 in OECD countries is a reduction in top statutory personal income tax rates. This trend was accompanied by reductions in the threshold where the top rate applies, as well as reductions in the statutory rate applicable at average wage earnings